Manajemen Strategik Tenaga Pendidik di SD Cendana Batam - Afridoni Afridoni; Muhammad Syaifuddin; Tuti Andriani (Departement of Mathematics Education, 2023)
In achieving maximum learning outcomes which is the ultimate goal of educational programs in schools, all educational resources must be managed effectively and efficiently. Teaching staff management is an activity that must be carried out starting from the teaching staff entering the educational organization until finally leaving through the process of human resource planning, recruitment, selection, placement, evaluation of teaching staff, awarding of compensation, awards, education and development training and termination. The methodology used in writing this article uses a qualitative approach with a qualitative descriptive method. The research subjects consisted of school principals, teacher boards, in this study using observation data collection methods, interviews and documentation, qualitative research data analysis techniques in collecting data using techniques; editing, categories, displaying data and interpretation. The findings in this study are that the management of education personnel (teachers and staff) absolutely must be implemented by school principals in order to utilize teaching staff effectively and efficiently to achieve optimal results. In accordance with this, a school principal must be able to find, position, evaluate, direct, motivate, and develop the talents of each teacher and staff and be able to align individual and organizational goals.